"No drain, no gain": Validation of novel quinsy simulation model. Issue 1 (19th December 2020) - Bhalla, Sanjana; O'Byrne, Lisa; Beegun, Issa; Amos, Dora; Jones, James Arwyn; Awad, Zaid; Tolley, Neil
Abstract: Objectives: To test a novel, low‐cost, home‐made model for needle aspiration of PTA. To ascertain whether simulation‐based teaching using this model was superior to lecture‐based teaching in increasing confidence and reducing anxiety relating to PTA aspiration. To assess whether there was an improvement in outcomes for PTA patients at one hospital following the delivery of a simulation‐based training session using our model. Methods: We designed two teaching sessions for junior doctors starting work in ENT: a simulation‐based teaching session using a low‐cost home‐made simulation model and a lecture‐based teaching session covering the same content. We asked the participants to complete pre‐ and post‐session surveys regarding confidence and anxiety levels and analyzed this data. We also retrospectively collected data over 3 months for patients referred to ENT with suspected PTA and assessed their outcomes. We assessed patient outcomes before and after the delivery of a simulation‐based training course using our model. Results: Simulation‐based teaching using our model was shown to be associated with a statistically significant increase in junior doctors' confidence levels. Reaccumulation and reattendance rates for PTA following aspiration were 16.67% and 22.7% respectively preintervention and 0% and 7.14% respectively postintervention. Conclusion: A regular simulation‐based teaching session should be introduced using a PTA aspiration model for junior doctors as it leads to increased confidence levels, and reduced reaccumulation and recurrence rates of PTA. Level of evidence: Level 4. Abstract :